The Relationship of Administrative Philosophy in Village Governance - Fahmi Fauzi; Mulyaningsih; Yagus Triana (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
This article discusses voter participation in the 2024 General Election (Pemilu) in Palu City through the Village Care for Elections and Elections (DP3) program initiated by the General Elections Commission (KPU). The DP3 program aims to increase community awareness and involvement, especially in rural areas that were previously recorded as having low levels of participation. This study uses a descriptive qualitative approach with data collection techniques in the form of interviews, observations, and documentation. The results of the study indicate that the DP3 program in Palu City was able to encourage increased voter participation through community-based voter education, involvement of community leaders, and a direct, participatory approach. However, the implementation of the program still faces several obstacles, such as limited human resources and logistics, as well as the level of political literacy that is not evenly distributed in society. This article concludes that the DP3 program has contributed positively to building a culture of democracy at the grassroots level and can be a model for sustainable electoral participation if accompanied by capacity building and cross-sector collaboration.